Work Safety Risk Assessment at Container Load Unloading Jobs at PT. Pelabuhan Indonesia II (Persero) Palembang Branch 2017 - Tedi levinrarian1, Zikri Fathur Rahman1, Abdul Rohim Tualeka1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Loading and unloading of container goods is carried out using cranes and truck containers as a means of transportation besides facilitating activities, which can also lead to the risk of workplace accidents. In 2014 there was a work accident in Kuningan Jakarta, workers were crushed by a container during the loading and unloading process. Container loading and unloading is a routine activity carried out at PT. Pelabuhan Indonesia II (Persero) Palembang Branch. This activity involves tools that can cause accidents such as being hit by a container and hit by a truck head, therefore a risk assessment is carried out on container loading and unloading work. The purpose of this study was to analyze occupational safety risk assessments on container loading and unloading work. This study uses a qualitative research design, using Job Safety Analysis (JSA) for the risk identification process, the US / NZ 4360: 1999 semi-quantitative risk assessment table for risk analysis and semi-quantitative risk level Cross (1988) for risk evaluation. The results of the study indicate that container loading and unloading work consists of the preparation stage, the operation phase of the QCC and the stage of moving containers. The risks identified based on the stage of work are overtaken by containers, falling from heights, collisions between head trucks, falling lifts, hit by a lock lock, getting hit by a truck head, falling into the river, collisions between QCCs and electric shock. The hazards included in the acceptable risk category include being crushed by repair equipment, hands pinched, tripping, slipping lubricants and head banging. The suggestion of this research is that all activities in the field should be carried out in accordance with the applicable regulations and supervision should be carried out more specifically in the use of PPE and conduct periodic health checks on workers.